Traditional Law and Russian Peasantry - Viktorovich Erin, Pavel; Vladimirovna Melekhova, Natalia; Pavlovich Nikolashin, Vadim (International Journal of Engineering and Technology, 2018)
This article analyzes the application of customary law in peasant legal pro-ceedings. The authors consider reasons for the domination of customary law in the everyday life of peasants in the early 20th century. They also determine the causes of the declining authority of customs in legal regulation. Law becomes the most convenient tool for resolving legal disputes. The paper presents the attitude to the customary law of leading lawyers and public officials and re-veals different viewpoints on the problem under consideration. The analysis of these positions enables researchers to consider the attitude to legal norms in modern society from a moral perspective.Â Â